﻿Antioxidant, cholesterol lowering activity, and analysis of Caesalpinia bonducella seeds extract - Weny J. A. Musa; Nurhayati Bialangi; Ahmad Kadir Kilo; Boima Situmeang; Ninik Triayu Susparini; Ilham Dwi Rusydi (Pensoft Publishers, 2023)
Tombili plant (Caesalpinia bonducella) belongs to the family of Fabaceae. The seed extract of tombili has been empirically used as a traditional medicine. The purpose of this research was to fractionate tombili seed extract and test their antioxidant and cholesterol lowering activities. Extraction was made into fractions using n-hexane, ethyl acetate, and methanol as a solvent. The chemical compound of the ethyl acetate fraction was analyzed using liquid chromatography-mass spectrometry (LC-MS/MS). Antioxidant activity was tested using the DPPH method. The highest antioxidant activity was shown in ethyl acetate fraction with an IC50 value of 86.153 μg/mL. The second was the methanol fraction with an IC50 value of 94.053 μg/mL, and the third was the n-hexane fraction with an IC50 value of 100.933 μg/mL. The cholesterol lowering activity analysis showed that all fractions could inhibit cholesterol. The highest anti-cholesterol activity shown in ethyl acetate fraction with the concentration of 600 μg/mL can inhibit 81.5% of the cholesterol activity. The LC-MS/MS analysis showed that the ethyl acetate fraction contained glucoside, homoplantaginin, and vernolic acid compounds.